Animal model of diabetic keratopathy - Dewi, Pitra Ariesta Shinta; Sitompul, Ratna; Pawitan, Jeanne; Naroeni, Aroem (ARSHI Veterinary Letters, 2019)
Diabetic keratopathy is one of the most common ocular complications in diabetes mellitus. Protocol for diabetes induction in rat model also has been established in many centers. Nonetheless, method in developing diabetic keratopathy rat model has not been well covered. Streptozotocin (STZ)-induced diabetes is widely being used as animal diabetic model. The purpose of this study is to obtain an animal model of diabetic keratopathy that can be used to study the morphology, metabolism, and function ofcornea in cases where human samples can be difficult to obtain. A single dose STZ (50 mg/kg) was injected intraperitoneally to control and intervention group. Plasma glucose level concentrations were tested in day 3 postinjections. Obtained animal model of diabetic keratopathy, with significant difference of blood glucose level between intervention and control group (P